One-minute seated push-up test: an alternative physical strength and endurance test in community-dwelling older individuals - Poncumhak, Puttipong; Chokphukiao, Pakwipa; Intaruk, Roongnapa; Amatachaya, Pipatana; Amatachaya, Sugalya (Archives of Allied Health Sciences, 2022)
The available strength and endurance measures commonly involve lower limb functions, whilst the impairments in older people mainly occur in the lower limbs. Therefore, the existing measures may limit clinical application in these individuals. Based on the effects of global physiological changes throughout the body, the researchers hypothesized that the upper limb function can be used as an alternative clinical measure to reflect functional strength and endurance of older people. This cross-sectional study assessed the correlation between the outcome of 1-minute seated push-up test (1minSPUT) and standard measures to reflect functional strength and endurance, including the five times sit-to-stand test (FTSST) and the two-minute step test (2MST), among 67 community-dwelling older adults. Participants with an average age of 75 years were interviewed and assessed for their demographics and the ability to perform the 1minSPUT, FTSST, and 2MST. The findings indicated significant correlation between the 1minSPUT and the FTSST (rs= -0.492 to -0.537, p-value < 0.05), and the 2MST (rs = 0.388 to 0.441, p-value < 0.05) for total and separately for male and female participants. The findings suggest the use of 1minSPUT, a practical measure that can be done in a limited area, as an alternative measure to reflect functional strength and endurance in older individuals.